Prospective evaluation of 25-gauge Franseen needles for endoscopic ultrasound-guided fine-needle biopsy of solid pancreatic masses - Inoue, Tadahisa; Tsuzuki, Toyonori; Takahara, Taishi; Ibusuki, Mayu; Kitano, Rena; Kobayashi, Yuji; Ohashi, Tomohiko; Nakade, Yukiomi; Sumida, Yoshio; Ito, Kiyoaki; Yoneda, Masashi (Endoscopy International Open, 2020)
Background and study aims The ideal puncture needle for endoscopic ultrasound (EUS)-guided sampling is maneuverable and easy to puncture with, and can obtain sufficient material in almost one pass. The novel 25-gauge Franseen needle may provide a good balance between maneuverability and sample yield.Patients and methods Between July 2017 and December 2018, 116 patients with solid pancreatic masses were prospectively enrolled and investigated. We evaluated the diagnostic yield associated with using the 25-gauge Franseen needle for EUS-guided sampling of pancreatic masses.Results The technical success rate was 100 % (116/116). The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy for malignancy were 98 % (105/107), 100 % (9/9), 100 % (105/105), 82 % (9/11), and 98 % (114/116), respectively. Cumulative sensitivities for malignancy were 87 % (93/107) on pass 1, 97 % (104/107) on pass 2, and 98 % (105/107) on pass 3, respectively, with no increase in sensitivity after 4 or more. An adequate specimen for histological assessment was obtained in 79 % (92/116) of cases. Multivariate logistic analyses showed that lesion size smaller than 13 mm was a risk factor for failure of obtaining an adequate specimen for histological assessment (P = 0.010)Conclusions The novel 25-gauge Franseen needle showed excellent diagnostic yield for solid pancreatic masses. However, its ability to obtain an adequate specimen for histological assessment may still be insufficient, especially when dealing with small lesions.